Addition Of Avocado Seed Flour In The Making Of Choux Paste - Lestari, Friska Rieny; Utari, Nisa Rahmaniyah; Irfan, Muhammad (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
Avocado is one of the good plant commodities in Indonesia, avocado production in Indonesia itself is quite abundant and has been widely used for various product processing. This can be seen from the production of avocados in Indonesia in 2021 reaching 660,830 tons, the part consumed from avocados is only the flesh, while the skin and seeds are used as waste. The percentage of avocado seed weight is about 20% of the total weight of the fruit. So to reduce the amount of avocado seed waste, the author conducted an experiment on avocado seeds that had been processed into flour and added them to the product that the author would study, namely choux paste. Meanwhile, the antioxidants found in avocado seeds have potential as natural food additivies for food products. In this study the addition of avocado seeds aims to determine the effect of the addition of taste and public acceptance of choux paste from avocado seed flour. The author chose choux paste in this study because choux products can be combined with various kinds of fillings that have a sweet taste, so they can overcome the bitter taste of avocado seed flour. This study was conducted to analyze the level of preference (taste, aroma, texture and taste) of choux pasta through organoleptic tests. This research is an  experimental research with 4 treatments of avocado seed flour, namely control (P0), 20% (P1), 30% (P2) and 50% (P3). The subjects of this study were 40 non-expert panelists and 5 expert panelists. The results of this study indicate that the best formula for avocado seed flour choux paste favored by the second panel is the addition of 20% avocado seed flour. The results of the average value obtained from 4 aspects (color, aroma, taste and texture) are with a total score of 39.8 expert panelists with an average of 3.3 which belongs to the like category. Meanwhile, the total score of non-expert panelists is 41.2 with an average of 3.4 which is included in the like category.